Kompetensi guru dan fasilitas belajar berpengaruh terhadap hasil belajar siswa - Risma Agustina; Imam Bukhori (Jurnal Ekonomi, Bisnis dan Pendidikan (JEBP), 2022)
Education is a fundamental effort in developing the degree of resources by encouraging learning activities with various sources of information and facilitating student learning activities to achieve maximum goals. In the teaching and learning process a relationship occurs between aducators and students. Not only ability of educators but a progress in teaching and learning activities are also factors that encourage the acquisition of student learning outcomes to match what is expected. The data collection instrument used a questionnaire given to respondent to fill out. The method used in this research is quantitative. The population and sample were students of class X and XII majoring in OTKP and BDP at SMK Ardjuna 2 Malang. The data analysis technique used is the classical assumption test, multiple linear regression test, t test and F test. The data collection instrument uses a questionnaire or questionnaire given to respondents to fill out. The results of the data analysis test stated that the competence of teachers and learning facilities had a positive and significant effect on student learning outcomes. Pendidikan adalah upaya yang mendasar dalam pengembangan derajat manusia, dengan cara mendorong aktivitas belajar dengan berbagai sumber informasi dan memfasilitasi kegiatan belajar siswa agar mencapai tujuan secara maksimal. Didalam proses belajar mengajar tentu terjadi sebuah hubungan diantara tenaga pendidik dengan siswa. Bukan hanya kemampuan tenaga pendidik saja, suatu kemajuan dalam kegiatan belajar mengajar diduga disokong oleh sarana atau pendukung pembelajaran yang dilaksanakan. Metode yang digunakan dalam penelitian ini ialah kuantitatif. Populasi penelitian ialah siswa kelas X dan XII jurusan OTKP dan BDP di SMK Ardjuna 2 Malang. Teknik analisis data yang digunakan ialah uji asumsi klasik, uji regresi linier berganda, pengujian t dan pengujian F. Instrument pengumpulan data menggunakan angket atau kuisioner yang diberikan kepada responden untuk diisi. Hasil uji analisis data menyatakan bahwa kompetensi guru dan fasilitas belajar berpengaruh positif dan signifikan dalam hasil belajar siswa.